1988
DOI: 10.1029/wr024i009p01535
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficiency of some estimators of fluvial total phosphorus load

Abstract: The accuracy of estimating total phosphorus (TP) loads to receiving waters usually is constrained by availability of concentration data, as discharge (flow) data normally are comparatively abundant. Using 4 years of daily observations from three tributaries to the Great Lakes (Grand, Saginaw, and Sandusky Rivers), annual TP loads were tested for accuracy by five methods, including regression, ratio, and robust estimators. Monte Carlo methods were employed to simulate replicated flow‐stratified sampling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Several authors found the stratified Beale's ratio estimator (BRE) to have small biases (Dolan et al, 1981;Preston et al, 1992;Young et al, 1988). These studies were based either on sediment or on phosphorus concentrations, both showing a positive correlation with discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors found the stratified Beale's ratio estimator (BRE) to have small biases (Dolan et al, 1981;Preston et al, 1992;Young et al, 1988). These studies were based either on sediment or on phosphorus concentrations, both showing a positive correlation with discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Walling and Webb, 1981;, nitrate-N (N03-N) transport (Smith and Stewart, 1977;Stevens and Smith, 1978) and total P (TP) transport (Dolan et al, 1981;Young et al, 1988;Preston et al, 1989;Rekolainen et al, 1991). Walling and Webb (1981), working on suspended sediment data from the river Creedy, UK, reported that the precision of transport estimates decreased with increasing sampling interval, and that regression methods were more precise than interpolation methods.…”
Section: Introductionmentioning
confidence: 97%
“…The Ratio method is also affected by poor characterization of the tail of the concentration distribution. Because the method is based on the mean of the unit loads, the weight that any individual observation has on the load estimate is reduced compared to the Rating method (Young et al ., ). However, in our study, loads estimated using the Ratio method at some sites had lower precision (larger SE P values) than those estimated using the L5 and L7 methods, particularly for TP (Figure ).…”
Section: Discussionmentioning
confidence: 99%